(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Climate change happened to be one of the most serious global challenges of modern times, with legal, political, and social consequences. However, international law has been used as a tool to guide how states respond to climate risks, reduce greenhouse gas emissions, and protect vulnerable populations. This review paper examines how Canada and the United States respond to climate change within the framework of international law as of 2025. Although both countries are economically advanced and historically high emitters of greenhouse gases, their legal approaches to climate governance vary considerably. Canada remains actively engaged in international climate agreements and incorporates these commitments into domestic legislation. On the contrary, the United States has adopted a reserved approach, including withdrawal from major international climate instruments and reduced reliance on international legal commitment. By reviewing legal instruments, policies, and scholarly literature, this paper highlights how differences in policy objectives and legal interpretation shape national climate responses. The paper concludes that these contrasting approaches have important implications for the effectiveness of international climate law and global climate cooperation.